2019
DOI: 10.1017/s0003055419000418
|View full text |Cite
|
Sign up to set email alerts
|

Persuading the Enemy: Estimating the Persuasive Effects of Partisan Media with the Preference-Incorporating Choice and Assignment Design

Abstract: Does media choice cause polarization, or merely reflect it? We investigate a critical aspect of this puzzle: How partisan media contribute to attitude polarization among different groups of media consumers. We implement a new experimental design, called the Preference-Incorporating Choice and Assignment (PICA) design, that incorporates both free choice and forced exposure. We estimate jointly the degree of polarization caused by selective exposure and the persuasive effect of partisan media. Our design also en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 46 publications
1
44
0
2
Order By: Relevance
“…After having described the sermons being delivered in a given context, researchers could employ participants’ decisions to listen to a particular type of sermon as a main outcome measure. DeBenedictis-Kessner et al (2019) have shown how lab and survey experiments can combine free choice over treatments with forced choice in order to estimate treatment effects among those who would have self-selected into exposure. DeBenedictis-Kessner et al (2019)’s focus was media influence, but the idea is easily extended to sermons.…”
Section: Disaggregating Religion and Isolating The Effects Of Sermonsmentioning
confidence: 99%
See 1 more Smart Citation
“…After having described the sermons being delivered in a given context, researchers could employ participants’ decisions to listen to a particular type of sermon as a main outcome measure. DeBenedictis-Kessner et al (2019) have shown how lab and survey experiments can combine free choice over treatments with forced choice in order to estimate treatment effects among those who would have self-selected into exposure. DeBenedictis-Kessner et al (2019)’s focus was media influence, but the idea is easily extended to sermons.…”
Section: Disaggregating Religion and Isolating The Effects Of Sermonsmentioning
confidence: 99%
“…DeBenedictis-Kessner et al (2019) have shown how lab and survey experiments can combine free choice over treatments with forced choice in order to estimate treatment effects among those who would have self-selected into exposure. DeBenedictis-Kessner et al (2019)’s focus was media influence, but the idea is easily extended to sermons. If applied to our approach, one could combine free choice of sermon content with forced assignment to sermon content to estimate the degree of influence of sermons on political behavior among those who are in practice most likely to choose to listen to those sermons.…”
Section: Disaggregating Religion and Isolating The Effects Of Sermonsmentioning
confidence: 99%
“…Erneut sollte darauf hingewiesen werden, dass ein substantieller Teil der Bevölkerung uberhaupt keine oder nur in geringem Maße politische Nachrichten konsumiert. Diese Menschen haben zwar oftmals ein geringeres politisches Vorwissen und weniger gefestigte Meinungen und sind somit leichter in ihren Positionen zu beeinflussen als Bürger mit starkem politischen Interesse und bereits gefestigten Meinungen (de Benedictis-Knesser et al 2019). Solange allerdins kein oder kaum Nachrichtenkonsum stattfindet, sind auch keine oder nur abgeschwächte Medieneffekte zu erwarten.…”
Section: Medien Und Polarisierungunclassified
“…Erneut sollte darauf hingewiesen werden, dass ein substantieller Teil der Bevölkerung uberhaupt keine oder nur in geringem Maße politische Nachrichten konsumiert. Diese Menschen haben zwar oftmals ein geringeres politisches Vorwissen und weniger gefestigte Meinungen und sind somit leichter in ihren Positionen zu beeinflussen als Bürger mit starkem politischen Interesse und bereits gefestigten Meinungen (de Benedictis-Knesser et al 2019). Solange allerdins kein oder kaum Nachrichtenkonsum stattfindet, sind auch keine oder nur abgeschwächte Medieneffekte zu erwarten.…”
Section: Soziale Netzwerkseitenunclassified